Morpho-biochemical and molecular diversity patterns of basmati rice (Oryza sativa) germplasm using protein and simple sequence repeat markers - KAPOOR, NEELESH; TIWARI, ADITI; AGRAWAL, ANKIT; KUMAR, PRAFULLA; BHARTI, MAHESH KUMAR; KUMAR, MUKESH; KUMAR, RAVINDRA; SENGAR, RAKESH SINGH (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during the rainy (kharif) season of 2020–21 at Sardar Vallabhbhai Patel University of Agriculture and Technology, Modipuram, Meerut, Uttar Pradesh to analyse the agro-morphological characteristics of 20 different basmati rice (Oryza sativa L.) varieties which are indigenous to different states but are grown in the western Uttar Pradesh to check their survivability using qualitative agro-morphological, biochemical and molecular markers. For morphological characterization, four growth parameters, viz. plant height, panicle length, grains/plant, and tillers/plant were selected and from these parameters, the variety Basmati-386 was selected as tallest (160.33), maximum panicle length was evaluated for the variety CSR-30 (31.41). The variety Basmati-1612 exhibited the maximum number of grains/plant, with a count of 1055.55 and the maximum number of tillers/plant was observed for Punjab Basmati-4 (15.20). For biochemical characterization, total seed protein of the varieties was subjected to protein profiling through SDS-PAGE among which Vallabh Basmati-21 and Tarawadi Basmati were found highly polymorphic. Molecular characterization was performed using 10 SSR markers, of which seven primers produced results with eight varieties and a total of 52 reproducible band positions were amplified, of which 51 were polymorphic. The number of alleles produced by SSR primers ranged from two (RM-122 and RM-127) to four (RM-3), with RM-23 producing the maximum number of polymorphic bands.